ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN MASALAH GEOMETRI DITINJAU DARI KEMAMPUAN MATEMATIKA SISWA - Vera Rosalina Bulu; Taty R Koroh (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This research aims to describe the difficulty of students in solving mathematical problems of geometric materials in view of the student's mathematical abilities. Description of the student's difficulties can help the teacher as information to provide solutions in overcoming the difficulties of students in solving geometry problems. This research is descriptive qualitative research. This research was imposed on students of class VIII of State Junior High School I Amanuban Barat. The sample in the study was 3 students with high, moderate and low ability. Samples are taken using purposive sampling techniques. Data retrieval techniques use observations, interviews and geometric material troubleshooting tests. Data analysis techniques use qualitative data analysis. The results showed that highly capable students have difficulty in re-examining the results of problem solving, students are having difficulty in determining the strategy to be used, using those strategies to solve problems and re-examine the results of solving the problem. Furthermore, low-skilled students have difficulties ranging from understanding problems, determining settlement strategies, using settlement strategies and re-examining the solving of mathematical problems. This is because learners do not understand the concept of geometry, are not used to practicing problem solving problems that result in students not having strategies in solving mathematical problems encountered. Furthermore, the advice that can be given is that teachers need to map the difficulty of solving problems in each existing material so as to help teachers and students in overcoming difficulties solving math problems.